Low risk of esophageal adenocarcinoma among patients with ultrashort‐segment Barrett's esophagus in Japan. Issue 4 (14th September 2021) - Fukuda, Sho; Watanabe, Kenta; Yoshida, Tatsuki; Takahashi, So; Fujimori, Shusei; Horikawa, Yohei; Komatsu, Taiga; Shirane, Kenji; Shimodaira, Yosuke; Matsuhashi, Tamotsu; Iijima, Katsunori
Abstract : Objects: Ultrashort‐segment Barrett's esophagus (USSBE; length of <1 cm) is very frequently diagnosed in Japan, but the cancer risk of USSBE is unknown. In this study, by retrieving endoscopic images, we retrospectively investigated the incidence of esophageal adenocarcinoma (EAC) by the grade of Barrett's esophagus (BE) and compared the findings with those of gastric cancer by the degree of endoscopic gastric atrophy in the same population. Methods: Among consecutive participants who had undergone endoscopy for an annual health checkup in 2014, the 9121 who had received at least one follow‐up endoscopy by December 2020 were enrolled in this study. Using the retrieved endoscopic images, we retrospectively evaluated BE and gastric atrophy. Information on the subsequent occurrence of EAC and gastric cancer as of December 2020 was also collected. The incidence of cancer by the extent of BE and gastric atrophy was calculated and expressed as the percentage per year. Results: On reviewing the endoscopic image in 2014, 4190 (45.9%) were found to have been diagnosed with BE, of whom 3318 (36.4%) were judged to have USSBE. During an observation period of 54.1 (17.9) months, 89 gastric cancers and only two EACs were identified. The incidence of EAC in USSBE was 0.0068%/year, which was nearly as low as the incidence of gastric cancer in atrophy‐free patients (0.0068% vs. 0.0059%/year). Conclusions: Although the prevalence of USSBE is quite high (36.4%), the incidence of EAC in USSBE is very low (0.0068%/year). Accordingly, USSBE can be excluded from targets for endoscopic surveillance in Japan.